E-COBRA: Integration of Wind Turbine Technology in Electric Car Power Banks for Sustainable Transportation - F.A.R. Puteri; T.K. Hana; N.K. Novianto (Journal of Marine Electrical and Electronic Technology, 2024)
Dependence on non-renewable energy remains a major challenge, despite the growing popularity of electric cars, as most electricity sources come from coal. In response, this paper proposes E-COBRA, a wind turbine system with a magnetic rotor as a renewable electricity source that can extend the battery life of electric cars. Functioning as a power bank, E-COBRA utilizes wind energy while the car is moving and converts it into electricity to support the battery. The design of the E-COBRA follows the principles of aerodynamics, with an installation on the roof of the electric car to capitalize on the kinetic energy from the wind hitting the car. The lift generated by the air on the roof of the electric car turns a wind turbine. Inside the generator, the mechanical energy is used to spin a magnetic rotor inside a stationary coil of stator wire, changing the magnetic field and inducing electricity in the wire. This process generates electricity that is conducted through a cable and connected directly to the car’s charging port. This paper compares the design of using a diffuser-increased wind turbine (DAWT) with a vertical axis wind turbine (VAWT) for the E-COBRA system. The comparison shows that the DAWT produces the largest energy, electrical power output of 2.2 kW at a car speed of 71.2 km/h. This technology not only reduces reliance on non-renewable energy but also offers a significant solution for increasing the efficiency and travel range of electric cars. As such, this approach represents a significant development in sustainable transportation solutions.